b - Viswanatha Reddi, B.; Chandamama India Ltd. (Madras, India) (Chennai : Chandamama India Ltd., 2003)
Selections from several modern Indic language editions of the children's magazine Chandamama translated into English; stories based on Hindu mythology, legends, and folk tales; includes briefly history of the magazine in pictures.
Short stories.
"Collector's edition."